Implementation of the Physics Edupark Concept for Pre-Design of a Physics E-Book Based on Local Potential and the Quality of Physics Tourism Education - Nadya Syahdi; Hamdi Rifai (Postgraduate, University of Mataram, 2026)
The implementation of digital technology has had a significant positive impact on education by expanding access to learning, allowing students to learn anytime and anywhere digitally. This study aims to observe and analyze the edupark at the Bukit Langkisau tourist attraction and the relationship between physics materials and the tourist attraction. After the analysis, this Edupark e-book can be developed. The results of this study indicate that printed books are still predominantly used in schools, and the use of non-printed books is still lacking; the average results of student knowledge and skills are still low; learning materials integrated with Edupark at tourist attractions are still rarely used; and have not been able to improve students' digital literacy. The conclusion of this study is the need to develop an integrated physics education e-book at tourist destinations. The Bukik Langkisau tourist attraction has the potential to be used as an educational park for learning, but has not been optimally implemented due to difficult access to the tourist location. Therefore, the purpose of this study is to develop an integrated physics education park e-book at the Bukit Langkisau tourist attraction.